Perspectives of oil pulling therapy in dental practice - T Lakshmi; R Rajendran; Vidya Krishnan (Wolters Kluwer Medknow Publications, 2013)
Oil pulling has its origin in Ayurvedic medicine, is a natural remedy to improve oral health. Its antibacterial properties help to eradicate the bacteria and other debris from adhering to the oral cavity. It reduces the accumulation of plaque, prevents halitosis, cavities, gingivitis. It is used to heal the bleeding gums and mouth ulcers. Oil pulling with sesame oil improves overall health. Other than oral health, oil pulling also helps in reducing asthma, allergies, chronic fatigue, diabetes, migraine headaches and chronic skin problems. It works by detoxifying or cleansing the body. The aim of this article is to highlight the benefits of oil pulling in management of oral health.